The fast rise of the unusual type IIL/IIb SN 2018ivc - Reguitti, A.; Dastidar, R.; Pignata, G.; Maeda, K.; Moriya, T. J.; Kuncarayakti, H.; Rodriguez, O.; Bersten, M.; Anderson, J. P.; Charalampopoulos, P.; Fraser, M.; Gromadzki, M.; et al. (EDP SCIENCES S A, 2025)
We present an analysis of the photometric and spectroscopic dataset of the type II supernova (SN) 2018ivc in the nearby (10 Mpc) galaxy Messier 77. Thanks to our high-cadence data, we observed the SN rising very rapidly by nearly three magnitudes in five hours (or 18 mag d(-1)). The r-band light curve presents four distinct phases: the maximum light, which was reached in just one day, followed by a first, rapid linear decline and a short-duration plateau. Finally, the long, slower linear decline lasted for one year. Thanks to the ensuing radio re-brightening, we were able to detect SN 2018ivc four years after the explosion. The early spectra show a blue, nearly featureless continuum, but the spectra go on to evolve rapidly; after about ten days, a prominent H alpha line starts to emerge, characterised by a peculiar profile. However, the spectra are heavily contaminated by emission lines from the host galaxy. The He I lines, namely lambda lambda 5876,7065, are also strong. In addition, strong absorption from the Na I doublet is evident and indicative of a non-negligible internal reddening. From its equivalent width, we derived a lower limit on the host reddening of A(V) similar or equal to 1.5 mag. From the Balmer decrement and a match of the B - V colour curve of SN 2018ivc to that of the comparison objects, we obtained a host reddening of A(V) similar or equal to 3.0 mag. The spectra are similar to those of SNe II, but with strong He lines. Given the peculiar light curve and spectral features, we suggest SN 2018ivc could be a transitional object between the type IIL and type IIb SNe classes. In addition, we found signs of an interaction with the circum-stellar medium (CSM) in the light curve, also making SN 2018ivc an interacting event. Finally, we modelled the early multi-band light curves and photospheric velocity of SN 2018ivc to estimate the physical parameters of the explosion and CSM.